2018
DOI: 10.1177/0885066618795126
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Site-Specific Complication Rates for Central Venous Catheter Insertions

Abstract: These results suggest that site-specific CVC complication rates may be less common than previously reported. These data further inform on the safety of modern CVC insertion techniques across all patient populations and clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…Infectious complications are reported to occur in 5% to 26% of patients, mechanical complications in 5% to 19%, and thrombotic complications in 2% to 26% [1], [13]. A recent study by Bell et al showed no statistically significant difference between internal jugular and subclavian vein approach CVC [12]. A study by Herts et al demonstrated a 6% complication rate of using power injection of contrast media through central venous catheters for CT examinations [17], without mention of SVC pericardial communication during the injection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Infectious complications are reported to occur in 5% to 26% of patients, mechanical complications in 5% to 19%, and thrombotic complications in 2% to 26% [1], [13]. A recent study by Bell et al showed no statistically significant difference between internal jugular and subclavian vein approach CVC [12]. A study by Herts et al demonstrated a 6% complication rate of using power injection of contrast media through central venous catheters for CT examinations [17], without mention of SVC pericardial communication during the injection.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanical complications of CVC include retained guidewire, arterial injury, and pneumothorax. Duration-associated complications include deep vein thrombosis or pulmonary embolism, and central line-associated bloodstream infections [9], [10], [11], [12]. Infectious complications are reported to occur in 5% to 26% of patients, mechanical complications in 5% to 19%, and thrombotic complications in 2% to 26% [1], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recognised complications from central venous line insertion include infection; line related thrombosis; bleeding; pneumothorax; haemothorax; retained guidewires, and; iatrogenic arterial injury [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Im Vergleich zu anderen Punktionsstellen, wie der V. jugularis interna oder der V. femoralis, verfügt der VSK über eine geringere Thromboseund Infektionsrate [19,20,27]. Auch bei der arteriellen Fehlpunktion ist der VSK überlegen [3,4,19,26]. Dagegen sind der sehr seltene Hämatothorax oder der in 0,1-3,1 % der Fälle vorkommende Pneumothorax häufiger beim VSK zu sehen [3,8,12,18].…”
Section: Hintergrund Und Fragestellungunclassified
“…Auch bei der arteriellen Fehlpunktion ist der VSK überlegen [3,4,19,26]. Dagegen sind der sehr seltene Hämatothorax oder der in 0,1-3,1 % der Fälle vorkommende Pneumothorax häufiger beim VSK zu sehen [3,8,12,18].…”
Section: Hintergrund Und Fragestellungunclassified